Catalyst for producing acetone and method for producing acetone
A catalyst composed of magnesium, calcium, manganese, zinc, iron, and aluminum composite oxides on carriers enhances acetone production stability and yield from ethanol and water, addressing the inefficiencies of existing methods.
Patent Information
- Application Number
- JP2021084547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-05-19
AI Technical Summary
Existing methods for producing acetone from ethanol and water lack sufficient catalytic performance and stability over time.
A catalyst comprising one or more metals from the group consisting of magnesium, calcium, manganese, zinc, iron, and aluminum, preferably in the form of composite metal oxides supported on carriers with specific surface areas, is used to stabilize acetone production.
The catalyst achieves high-yield acetone production over extended periods, with improved catalytic activity and durability.
Smart Images

Figure 0007611764000001 
Figure 0007611764000002 
Figure 0007611764000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst for producing acetone and a method for producing acetone. [Background technology]
[0002] Conventionally, there have been several reports on the synthesis reaction of acetone from ethanol and water. Non-Patent Document 1 studies the use of a catalyst in which calcium oxide is added to zinc oxide. Non-Patent Document 2 studies the use of an oxide catalyst made of iron and various metal components. It is disclosed that in a continuous reaction using a catalyst in which iron and zinc are combined, the acetone yield after 24 hours changes from 86% to 57%. Patent Document 1 studies the use of a catalyst containing iron, zinc, and an alkali metal and / or an alkaline earth metal, with the molar ratio of the alkali metal and / or the alkaline earth metal to zinc being 0.2 to 2. [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Journal of the Chemical Society, Chemical Communications, pp. 394-395 (1987) [Non-Patent Document 2] Journal of Materials Chemistry, Volume 4, Pages 853-858 (1994) [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2012-240913 Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, several methods for producing acetone from ethanol and water are known, but they do not have sufficient catalytic performance and there is room for improvement in order to stably produce acetone.
[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a catalyst for acetone production, which can produce acetone stably for a long period of time in the production of acetone from ethanol and water, and a method for producing acetone. [Means for solving the problem]
[0007] The present inventors have conducted various studies to achieve the above object and have come up with the present invention. That is, the present disclosure relates to a catalyst for producing acetone, which contains one or more metals (Me) selected from the group consisting of magnesium, calcium, manganese, and zinc, iron, and aluminum, and a method for producing acetone. Effect of the Invention
[0008] An object of the present disclosure is to provide a catalyst for producing acetone, which produces acetone in a high yield and stably for a long period of time, and a method for producing acetone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present disclosure will be described in detail below. Note that a combination of two or more of the individual preferred embodiments of the present disclosure described below is also a preferred embodiment of the present disclosure.
[0010] [Catalyst for producing acetone according to the present disclosure] <Catalyst> The catalyst of the present disclosure comprises the elements of one or more metals selected from the group consisting of magnesium, calcium, manganese and zinc (Me), iron, and aluminum.
[0011] The catalyst of the present disclosure is not particularly limited, and may contain other metal elements.
[0012] The state of the metal element contained in the catalyst of the present disclosure is not particularly limited, and examples thereof include a metal oxide containing the metal element, a support containing the metal element, a support supporting the metal element, etc. The metal oxide may be supported on a support.
[0013] The metal oxide may be a composite metal oxide.
[0014] Examples of the composite metal oxide include spinel type, perovskite type, magnetoplumbite type, and garnet type, with the spinel type being preferred.
[0015] The composite metal oxide is preferably an iron composite oxide (sometimes called ferrite) represented by the general formula MeO·nFe2O3 (Me represents one or more metals selected from the group consisting of magnesium, calcium, manganese, and zinc, and n represents an integer of 1 to 6). Specific examples include MgO·Fe2O3 and ZnO·Fe2O3.
[0016] Examples of the carrier include activated carbon, silica, alumina, silica-alumina, zeolite, silica-calcia, zirconia, ceria, magnesia, and diatomaceous earth.
[0017] The shape of the carrier is not particularly limited, but examples thereof include spherical, pellet, and honeycomb shapes.
[0018] The BET specific surface area of the support is preferably 20 to 200 m2 / g, more preferably 40 to 200 m2 / g. By using a support having a high specific surface area, the catalyst components are easily supported in a dispersed state, which is preferable because it increases the catalytic activity.
[0019] The state of the aluminum element contained in the catalyst of the present disclosure is not particularly limited. It may be contained as a compound containing aluminum alone as a metal, may be contained as an element of a composite metal oxide containing other metal elements, or may be contained as a carrier.
[0020] An example of a compound containing only aluminum as a metal is aluminum oxide. An example of a composite metal oxide containing other metal elements is a composite metal oxide of aluminum and Sn, Pb, Zn, Fe, In, or the like. Examples of a support include alumina (Al2O3), silica-alumina, and the like. From the viewpoint of catalyst performance, Al2O3 is more preferable.
[0021] In the catalyst of the present disclosure, the amount of one or more metals (Me) selected from the group consisting of magnesium, calcium, manganese and zinc per mole of iron is preferably 0.4 to 0.7 moles, more preferably 0.4 to 0.6 moles, and even more preferably 0.45 to 0.55 moles. By setting the amount of one or more metals (Me) selected from the group consisting of magnesium, calcium, manganese and zinc in the above molar range per mole of iron, good catalytic activity can be obtained.
[0022] In the catalyst of the present disclosure, the amount of aluminum per mole of iron is preferably 0.01 to 0.5 moles, more preferably 0.05 to 0.5 moles, and even more preferably 0.1 to 0.4 moles. By setting the amount of aluminum per mole of iron in the above molar range, good durability can be achieved.
[0023] The total amount of one or more metals (Me) selected from the group consisting of magnesium, calcium, manganese and zinc, iron, and aluminum contained in the catalyst of the present disclosure is preferably 50 to 100 mass%, and more preferably 80 to 100 mass%, relative to 100 mass% of the catalyst.
[0024] <Catalyst manufacturing method> The catalyst of the present disclosure may be produced by any method, including impregnation, precipitation, and coprecipitation. More preferably, the coprecipitation method is used. This method is preferable because it allows the production of a catalyst having excellent performance, since it is possible to obtain a coprecipitate (sometimes called a catalyst precursor) in which the metal elements constituting the catalyst are uniformly and highly dispersed. The dispersion state of each catalyst component in the produced catalyst can be evaluated, for example, using an electron microprobe analyzer (EPMA). When using EPMA, the dispersibility of the metal component, for example aluminum, contained in the catalyst is measured by measuring the amount of X-rays in a plane of 900 μm in each of the X-axis and Y-axis directions on the catalyst surface, and the average value (S) and its standard deviation (σ) are obtained from any measured point. The dispersibility of aluminum contained in the catalyst can be evaluated by the ratio (σ / S) of the standard deviation (σ) to the average value (S). The value of the ratio (σ / S) is preferably less than 0.25, more preferably less than 0.2, and even more preferably less than 0.15.
[0025] The coprecipitation method may include the steps of adding a basic aqueous solution to a solution containing a metal (Me), iron, and aluminum to obtain a coprecipitate, filtering the coprecipitate, drying the obtained coprecipitate, and calcining the same.
[0026] The amount of the metal element in the solution can be appropriately changed.
[0027] [Method of Producing Acetone Disclosed Herein] In the production method of the present disclosure, acetone-containing gas is obtained by reacting ethanol with water in the presence of a catalyst.
[0028] <Reaction of ethanol with water> The method for producing acetone disclosed herein can obtain a reaction product containing acetone, hydrogen, and carbon dioxide by contacting raw materials, ethanol and water, with a catalyst.
[0029] The method for producing acetone according to the present disclosure is not particularly limited and may be either a batch method or a continuous method, but from the viewpoint of productivity, a continuous method is preferred.
[0030] The method for producing acetone according to the present disclosure is preferably a gas phase reaction. Examples of the reaction format for the gas phase reaction include a fixed bed, a moving bed, and a fluidized bed, but the more convenient fixed bed format is preferred.
[0031] When the acetone production method of the present disclosure is a fixed bed type, the raw material gas may be mixed with gaseous ethanol and gaseous water (sometimes referred to as steam) and then supplied to the reactor to be contacted with the catalyst, or the gaseous ethanol and steam may be separately supplied to the reactor to be contacted with the catalyst.
[0032] Gaseous ethanol can be obtained, for example, by heating liquid ethanol in a vaporizer, and gaseous water can be obtained, for example, by heating water in a vaporizer.
[0033] The raw material gas may contain an inert gas such as nitrogen, helium, etc. Here, the raw material gas includes all gases supplied to the reactor.
[0034] The concentration of ethanol contained in the raw material gas is preferably 3 to 66 mol %, and more preferably 5 to 50 mol %. The molar ratio of water to ethanol contained in the raw material gas is preferably 0.5-10, and more preferably 1-5.
[0035] The ethanol used for the raw material gas is not particularly limited, and examples thereof include ethanol obtained by the hydration reaction of ethylene and bioethanol made from biomass raw materials, such as sugar-based materials such as sugar cane, starch-based materials such as grains, and cellulose-based materials such as plants.
[0036] The ethanol used in the raw material gas preferably contains bioethanol. The content of bioethanol in 100% by mass of ethanol is more preferably 50% by mass or more, even more preferably 75% by mass or more, and even more preferably 90% by mass or more.
[0037] The reaction pressure in the method for producing acetone according to the present disclosure can be any of reduced pressure, normal pressure, and increased pressure, but is preferably 0.07 MPa to 0.2 MPa, and more preferably 0.1 MPa to 0.15 MPa.
[0038] The reaction temperature in the method for producing acetone according to the present disclosure is preferably 250 to 600°C, more preferably 300 to 550°C, and further preferably 330 to 500°C.
[0039] In the method for producing acetone according to the present disclosure, the space velocity is preferably from 300 to 10,000 (1 / h), more preferably from 400 to 8,000 (1 / h), and further preferably from 500 to 6,000 (1 / h).
[0040] <Other processes> (purification process) The reaction products after contacting ethanol and water with the catalyst may contain not only acetone, hydrogen, and carbon dioxide, but also the raw materials ethanol and water.
[0041] The amount of acetone contained in the reaction product is preferably 2 mol % or more, more preferably 4 mol % or more, and further preferably 8 mol % or more, based on 100 mol % of the reaction product.
[0042] The method for producing acetone according to the present disclosure may include a step of obtaining purified acetone (sometimes referred to as purified acetone) from the reaction product by a known method, such as gas-liquid separation or distillation.
[0043] Gas-liquid separation can be carried out by a known method, for example, to separate the reaction product into gases such as hydrogen and carbon dioxide, and a liquid mixture mainly containing acetone. Distillation can be carried out by a known method to obtain purified acetone from a liquid mixture containing acetone.
[0044] The content of acetone contained in the purified acetone is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, based on 100% by mass of the purified acetone.
[0045] (Catalyst regeneration process) In the acetone production method of the present disclosure, if a change in the activity of the catalyst is observed, a step of regenerating the catalyst may be included. The method of regeneration is not particularly limited, but the catalyst can be regenerated by contacting it with an oxidizing gas such as oxygen at high temperature. For example, when the raw material gas is supplied to a fixed-bed type reactor, the raw material gas may be changed to an oxidizing gas, or the catalyst may be extracted from the reactor.
[0046] [Acetone production apparatus according to the present disclosure] The production apparatus is preferably a fixed-bed reactor, which may be connected to a vaporizer for obtaining a raw material gas.
[0047] The material of the manufacturing device is not particularly limited, but preferably includes stainless steel.Representative examples of stainless steel include autenite stainless steel, such as SUS304, SUS304L, SUS316 and SUS316L of Japanese Industrial Standards (hereinafter referred to as JIS); ferritic stainless steel, such as SUS405, SUS401L and SUS430 of JIS; martensitic stainless steel, such as SUS403, SUS410, SUS416 and SUS431 of JIS.
[0048] [Uses of acetone according to the present disclosure] The use of the acetone of the present disclosure is not particularly limited, but it can be suitably used as a raw material for the production of isopropyl alcohol. The acetone of the present disclosure can be hydrogenated by a known method to produce isopropyl alcohol. EXAMPLES
[0049] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and it is possible to carry out the present invention by making appropriate modifications within the scope of the above and below-mentioned aims, and all of these modifications are included in the technical scope of the present invention.
[0050] Example 1 12.3 g of zinc nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0% or more), 4.7 g of aluminum nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, Ltd., purity 97.0% or more), and 33.4 g of iron nitrate nonahydrate (manufactured by Nacalai Tesque, purity 98.0% or more) were dissolved in 400 mL of pure water to prepare a mixed aqueous solution of zinc nitrate, iron nitrate, and aluminum nitrate. While stirring the mixed aqueous solution with a magnetic stirrer, ammonia water (manufactured by Wako Pure Chemical Industries, Ltd., purity 28.0%) was added dropwise at room temperature to adjust the pH to 8. The resulting precipitate was collected by filtration, dried at 120°C for 10 hours, and then calcined at 450°C for 2 hours to obtain catalyst 1. Elemental analysis of the obtained catalyst 1 was performed using an X-ray fluorescence analyzer. The measurement sample was prepared by uniformly pulverizing catalyst 1 powder in an agate mortar, filling it into a polyvinyl chloride disk, and compressing it at 30 MPaG using a compression molding machine to form a disk. As a result, the molar ratios of zinc and aluminum to iron in catalyst 1 were 0.44 and 0.12, respectively. The crystal structure of the obtained catalyst 1 was analyzed by powder X-ray diffraction. The obtained diffraction pattern was almost identical to the pattern of ZnFe2O4 (JCPDF 00-022-1012), and no diffraction peaks derived from ZnO or Al2O3 were detected. Acetone production using catalyst 1 was carried out using a SUS316 tubular reactor (outer diameter 10 mm, inner diameter 8 mm). The powder of catalyst 1, which was uniformly crushed in an agate mortar, was filled into a vinyl chloride disk, compressed into a disk by a compression molding machine at 30 MPaG, crushed and classified into 0.71 to 1.18 mm, and 1.4 g of the granular catalyst was filled into a SUS tubular reaction tube. The reaction tube filled with catalyst 1 was placed in a circular electric furnace, nitrogen was supplied at 26.25 mL / min. (0 ° C, 1 atmosphere equivalent), the temperature was raised to 400 ° C by electric furnace heating, and maintained for 30 min. Thereafter, nitrogen, ethanol, and water were supplied at 26.25 mL / min. (0 ° C, 1 atmosphere equivalent), 5.22 mL / min. (0 ° C, 1 atmosphere equivalent), and 20.89 mL / min. (0 ° C, 1 atmosphere equivalent), respectively, and the reaction was carried out. The reaction was carried out continuously for 142 hours, and the ethanol conversion rate and acetone yield were measured over time. The results are shown in Table 1.
[0051] [Table 1]
[0052] Here, the ethanol conversion rate and the acetone yield were calculated according to the formulas (1) and (2). (Formula 1) TIFF0007611764000002.tif10150
[0053] (Formula 2) TIFF0007611764000003.tif10150
[0054] The synthesis reaction of acetone from ethanol and water is represented by the following reaction equation (3). (Formula 3) TIFF0007611764000004.tif7150
[0055] The acetone yield in formula (2) is evaluated based on the amount of carbon in the acetone produced relative to the total carbon in the ethanol fed to the reactor inlet. Therefore, the maximum acetone yield is 75%.
[0056] The gas at the reactor outlet was introduced into an absorption bottle containing pure water placed in an ice-water bath, and the components captured by the water were quantified by gas chromatography. The components not captured by the absorption bottle containing pure water were quantified by introducing the gas at the outlet of the absorption bottle into a gas chromatograph. From these analytical values, the flow rates of each component contained in the gas at the reactor outlet were calculated, and the ethanol conversion rate and acetone yield were calculated using the above formulas (1) and (2).
[0057] Comparative Example 1 9.2 g of zinc nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0% or more) and 25.1 g of iron nitrate nonahydrate (manufactured by Nacalai Tesque, purity 98.0% or more) were dissolved in 400 mL of pure water to prepare a mixed aqueous solution of zinc nitrate and iron nitrate. While stirring the mixed aqueous solution of zinc nitrate and iron nitrate with a magnetic stirrer, ammonia water (manufactured by Wako Pure Chemical Industries, Ltd., purity 28.0%) was added dropwise at room temperature to adjust the pH to 8. The resulting precipitate was collected by filtration, dried at 120 °C for 10 hours, and then calcined at 450 °C for 2 hours to obtain catalyst 2.
[0058] Elemental analysis of the obtained catalyst 2 was carried out by fluorescent X-ray analysis in the same manner as in Example 1, and the molar ratio of zinc to iron was found to be 0.44.
[0059] When the crystal structure of Catalyst 2 was examined by powder X-ray diffraction in the same manner as in Example 1, the obtained diffraction pattern was almost identical to the pattern of ZnFe2O4 (JCPDF 00-022-1012), and no diffraction peaks of ZnO were detected.
[0060] Acetone production using catalyst 2 was carried out in the same manner as described in Example 1. The reaction was carried out continuously for 137.5 hours, and the ethanol conversion rate and acetone yield were measured over the course of the reaction time. The results are shown in Table 2.
[0061] [Table 2]
[0062] Comparative Example 2 3.74 g of zinc nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, purity 99.0% or more) and 1.09 g of strontium nitrate (manufactured by Wako Pure Chemical Industries, purity 98.0% or more) were dissolved in 4.0 g of pure water to prepare an aqueous solution containing zinc and strontium. The aqueous solution containing zinc and strontium was added to 10.03 g of iron oxide hydroxide (manufactured by Kanto Chemical, purity 95.0% or more) that had been thoroughly dried at 120°C, and the mixture was kneaded with a glass rod for 5 minutes to form a slurry-like substance. This slurry-like substance was dried at 120°C for 10 hours and then calcined at 600°C for 3 hours to obtain catalyst 3.
[0063] Elemental analysis of the obtained catalyst 3 was carried out by fluorescent X-ray analysis in the same manner as in Example 1, and it was found that the molar ratios of zinc and strontium to iron were 0.12 and 0.05, respectively.
[0064] The crystal structure of Catalyst 3 was analyzed by powder X-ray diffraction in the same manner as in Example 1, and the diffraction peaks of Fe2O3 (JCPDF 00-001-1053) and ZnO (JCPDF 00-005-0593) were detected in the obtained diffraction pattern.
[0065] Acetone production using catalyst 3 was carried out in the same manner as described in Example 1. The reaction was carried out continuously for 137 hours, and the ethanol conversion rate and acetone yield were measured over the reaction time. The results are shown in Table 3.
[0066] [Table 3]
[0067] Comparative Example 3 3.00g of zinc nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, purity 99.0% or more), 0.87g of strontium nitrate (manufactured by Wako Pure Chemical Industries, purity 98.0% or more), and 6.50g of aluminum nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, purity 97.0% or more) were dissolved in 6.0g of pure water to prepare an aqueous solution containing zinc and strontium. The aqueous solution containing zinc, strontium, and aluminum was added to 8.02g of iron oxide hydroxide (manufactured by Kanto Chemical, purity 95.0% or more) that had been thoroughly dried at 120°C, and the mixture was kneaded with a glass rod for 5 minutes to form a slurry-like substance. This slurry-like substance was dried at 120°C for 10 hours and then calcined at 600°C for 3 hours to obtain catalyst 4.
[0068] Elemental analysis of the obtained catalyst 4 was carried out by fluorescent X-ray analysis in the same manner as in Example 1, and it was found that the molar ratios of zinc, strontium, and aluminum to iron were 0.12, 0.05, and 0.2, respectively.
[0069] The crystal structure of Catalyst 4 was analyzed by powder X-ray diffraction in the same manner as in Example 1, and the diffraction peaks of Fe2O3 (JCPDF 00-001-1053) and ZnO (JCPDF 00-005-0593) were detected in the obtained diffraction pattern.
[0070] Acetone production using catalyst 4 was carried out in the same manner as described in Example 1. The reaction was carried out continuously for 112 hours, and the ethanol conversion rate and acetone yield were measured over the reaction time. The results are shown in Table 4.
[0071] [Table 4]
[0072] Example 2 The catalyst 1 prepared in Example 1 was compressed, crushed, and classified to 0.71 to 1.18 mm, and 0.7 g of the granular catalyst was packed into a SUS tubular reaction tube. The reaction tube packed with catalyst 1 was placed in a circular electric furnace, nitrogen was supplied at 70 mL / min. (0 ° C., 1 atmosphere equivalent), and the temperature was raised to 400 ° C. by electric furnace heating and maintained for 30 min. Thereafter, the reaction temperature was changed to a predetermined temperature, and nitrogen, ethanol, and water were supplied at 70 mL / min. (0 ° C., 1 atmosphere equivalent), 13.9 mL / min. (0 ° C., 1 atmosphere equivalent), and 55.7 mL / min. (0 ° C., 1 atmosphere equivalent), respectively, to carry out the reaction. The ethanol conversion rate and acetone yield at 400, 425, and 450 ° C. were measured. The results are shown in Table 5.
[0073] [Table 5]
[0074] Comparative Example 5 30.12 g of zinc nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, purity 99.0% or more) was dissolved in 400 mL of pure water to prepare an aqueous zinc nitrate solution. While stirring the aqueous zinc nitrate solution with a magnetic stirrer, ammonia water (manufactured by Wako Pure Chemical Industries, purity 28.0%) was added dropwise at room temperature to adjust the pH to 7. The resulting precipitate was collected by filtration and dried at 120°C for 10 hours to prepare zinc hydroxide. 0.335 g of calcium hydroxide (manufactured by Wako Pure Chemical Industries, purity 99.0% or more) was added to 4.0 g of the obtained zinc hydroxide, and a small amount of water was added and thoroughly kneaded in a mortar. The obtained kneaded product was dried at 120°C for 10 hours and then calcined at 500°C for 2 hours to obtain catalyst 5.
[0075] An acetone production test was carried out in the same manner as in Example 2, except that catalyst 5 was used instead of catalyst 1, and the ethanol conversion rate and acetone yield were measured at 450° C. and 475° C. The results are shown in Table 6.
[0076] [Table 6]
Claims
1. Metals (Me) consisting of zinc, iron, and aluminum, A catalyst for producing acetone, comprising spinel ferrite (MeFe 2 O 4 ) and Al 2 O 3 .
2. 2. The catalyst for producing acetone according to claim 1, wherein the number of moles of aluminum per mole of iron is 0.01 to 0.
5.
3. 3. The catalyst for producing acetone according to claim 1 or 2, wherein the number of moles of the metal (Me) per mole of iron is 0.4 to 0.
7.
4. A method for producing acetone from ethanol and water in the presence of a catalyst, the catalyst comprising a metal (Me) consisting of zinc, iron, and aluminum, A method for producing acetone, comprising: spinel ferrite (MeFe2O4) and Al2O3.
5. 5. The method for producing acetone according to claim 4, wherein the number of moles of aluminum per mole of iron contained in the catalyst is 0.01 to 0.
5.
6. 6. The method for producing acetone according to claim 4 or 5, wherein the number of moles of the metal (Me) per mole of iron contained in the catalyst is 0.4 to 0.
7.
7. The method for producing acetone according to any one of claims 4 to 6, wherein the ethanol is derived from biomass.
Citation Information
Patent Citations
Preparation of carbonyl compound
JP1984033240A
Production of ketones
JP1989175949A
Method for producing acetone
JP2012188391A
Method for producing oxygen-containing compound having three or more carbon atoms
JP2012240913A
Method for manufacturing aldehyde
JP2014139158A